Contextualising brand consumption experiences: a multi-modal enabling technique. Issue 2 (8th April 2014) - Bulmer, Sandy; Buchanan-Oliver, Margo
Abstract : Purpose: – The purpose of this paper is to elaborate on a novel multi-modal enabling technique for contextualising brand consumption experiences. Design/methodology/approach: – A multi-modal interpretive narrative approach is presented as a means of investigating brands as experiential entities for use in consumer identity projects. It reports the strategic use of different modes of data collection: autobiographical narratives generated by solo participants to create a benchmark of identity and subsequent friendship pair guided discussion interviews. This offers a faster, cheaper and more convenient means of gaining access to consumer experiences of brands than traditional ethnographic methods, which require prolonged engagements within a community. Findings: – Consumer narratives of actual brand consumption and of mediated brand consumption are enhanced using this method. The consumer narratives generated provided rich insights into the role of brands in contributing to national identity. The contextualised use and function of identity narratives provided by brands were identified in addition to the identification of national community rituals of consumption. Originality/value: – The multi-modal use of friendship pair interviews with solo autobiographical interviews is shown to offer benefits to qualitative consumer researchers focussing on brand/identity issues. The combination of data collection methods allowed for greater reflexive, memorial and contextualised discussion in the friendship pair interviews about brand narrative consumption and generated responses that advance beyond socio-political conventions concerning brands. Consequently, contextualised brand consumption experiences can be accessed more effectively than in conventional depth interviews.